Pengaruh NPL, LDR, CAR dan NIM Terhadap ROA Pada Bank Perkreditan Rakyat - Rachmiyantono (Akademi Akuntasi Effendiharahap, 2021)
The problem of this research is whether NPL, LDR, CAR and NIM have an effect on ROA (a case study on Rural Banks? The research objective is to overcome the effect of NPL, LDR, CAR and NIM on ROA. This study uses secondary data, namely financial reports from 2011 -2015 from Rural Banks Analysis of the data using multiple linear regression analysis The results of the CAR analysis obtained do not have a significant effect on ROA NPL has a significant effect on ROA BOPO has a significant effect on ROA NIM has no significant effect on ROA.LDR has significant effect on ROA